Cyclization Reaction-Based Turn-on Probe for Covalent Labeling of Target Proteins. Issue 3 (19th March 2020) - Kojima, Hiroyuki; Fujita, Yuki; Takeuchi, Ryosuke; Ikebe, Yuka; Ohashi, Nami; Yamamoto, Keiko; Itoh, Toshimasa
Summary: Fluorescent molecules have contributed to basic biological research but there are currently only a limited number of probes available for the detection of non-enzymatic proteins. Here, we report turn-on fluorescent probes mediated by conjugate addition and cyclization (TCC probes). These probes react with multiple amino acids and exhibit a 36-fold greater emission intensity after reaction. We analyzed the reactions between TCC probes and nuclear receptors by electrospray ionization mass spectrometry, X-ray crystallography, spectrofluorometry, and fluorescence microscopy. In vitro analysis showed that probes consisting of a protein ligand and TCC could label vitamin D receptor and peroxisome proliferator-activated receptor γ. Moreover, we demonstrated that not only a ligand unit but also a peptide unit can label the target protein in a complex mixture. Graphical Abstract: Highlights: TCC probes react with amino acids and exhibit a 36-fold greater fluorescence TCC probe can label various proteins by exchanging protein ligand or peptide TCC probes have only a limited impact on protein function due to their small size In living cells, nuclear receptors can be labeled by TCC probes Abstract : Non-enzymatic proteins are challenging targets for turn-on probes. Here, Kojima et al. report turn-on fluorescent probes mediated by conjugate addition and cyclization (TCC probes). These probes react with nuclear receptors and emit bright fluorescence after the reaction. TCC probes are potent tools for molecular imaging and chemical proteomics.